Peran Manajemen Kesehatan Ternak Dalam Meningkatkan Produktiviitas Peternakan Kambing Etawa - Yusnelly, Yusnelly; Taufik, Taufik (CV. SINAR HOWUHOWU, 2024)
Livestock health management plays an important role in improving the productivity of Peranakan Etawah (PE) goats, especially in terms of milk and meat production. This study aimed to analyze the impact of implementing comprehensive health management on the productivity of PE goats in various farms. The research method involved observations and interviews with farmers, as well as analysis of productivity data obtained from the implementation of animal health practices, such as vaccination, fermented feed, and natural ingredient-based treatment. The results showed that farmers who implemented good health management managed to increase milk production by 25% and reduce mortality rates by 15%. The main factors influencing this success were regular vaccination, implementation of biosecurity, and structured feed management. However, constraints faced by farmers, such as limited access to technology and high operational costs, hinder the adoption of comprehensive health management. This study recommends increased extension programs and support from the government and relevant agencies to facilitate wider adoption of health management. With multi-stakeholder collaboration, it is expected that PE goat productivity can continue to increase, support food security, and provide economic benefits for farmers in rural areas.